The Star, 28 Mei 2009 - Aftar Singh (Star Publications (Malaysia) Berhad, 2009)
Junior World Cup trainees Mohd Sybrie Shamsuddin and R.Nadesh will get one last chance to prove that have recovered from their injuries when they play in two friendly matches next week.